DNA Methylation Regulates Transcription Factor-Specific Neurodevelopmental but Not Sexually Dimorphic Gene Expression Dynamics in Zebra Finch Telencephalon - Diddens, Jolien; Coussement, Louis; Frankl-Vilches, Carolina; Majumdar, Gaurav; Steyaert, Sandra; Ter Haar, Sita M.; Galle, Jeroen; De Meester, Ellen; De Keulenaer, Sarah; Van Criekinge, Wim; Cornil, Charlotte A.; Balthazart, Jacques; et al. (Frontiers in Cell and Developmental Biology, 2021)
Song learning in zebra finches (Taeniopygia guttata) is a prototypical example of a complex learned behavior, yet knowledge of the underlying molecular processes is limited. Therefore, we characterized transcriptomic (RNA sequencing) and epigenomic (RRBS, reduced representation bisulfite sequencing; immunofluorescence) dynamics in matched zebra finch telencephalon samples of both sexes from 1 day post hatching (1 dph) to adulthood, spanning the critical period for song learning (20 dph and 65 dph). We identified extensive transcriptional neurodevelopmental changes during postnatal telencephalon development. DNA (hydroxy)methylation was very low, yet increased over time, particularly in song control nuclei. Only a small fraction of the massive differential expression in the developing zebra finch telencephalon could be explained by differential CpG and CpH DNA methylation. However, a strong association between DNA methylation and age dependent gene expression was found for various transcription factors (i.a. OTX2, AR and FOS) involved in neurodevelopment. Incomplete dosage compensation, independent of DNA methylation, was found to be largely responsible for sexually dimorphic gene expression, with dosage compensation increasing throughout life. In conclusion, our results indicate that DNA methylation regulates neurodevelopmental gene expression dynamics through steering transcription factor activity, but does not explain sexually dimorphic gene expression patterns in zebra finch telencephalon.